Strategies to accelerate cervical cancer elimination in Greece: a modeling study - Palmer, Cody; Skroumpelos, Anastasios; Sabale, Ugne; Gountas, Ilias; Trimis, Georgios; Karokis, Antonis; Agorastos, Theodoros (Frontiers in Oncology, 2025)
IntroductionMost cervical cancer cases are caused by human papillomavirus (HPV), a vaccine-preventable infection. According to the World Health Organization (WHO), both high HPV vaccination coverage and cervical cancer screening rates will accelerate the elimination of cervical cancer, a threshold defined as <4 age-standardized cases per 100,000 women.MethodsA dynamic transmission model was used to study the effect of increased HPV vaccination coverage and cervical cancer screening rates in Greece on cervical cancer incidence over a 100-year time horizon. Greek-specific or proxy data were used for both model inputs and calibration prior to the evaluation of eight different vaccination and screening scenarios. The estimated time to cervical cancer elimination and eradication in Greece was reported as the year each scenario reached <4 cases per 100,000 and <1 case per 100,000, respectively.ResultsGreece reached the WHO cervical cancer elimination threshold by 2074 with a 50% HPV vaccination coverage and 50% Pap test screening rate. When HPV DNA-based methods replaced Pap tests at the same rate and HPV vaccination coverage levels, the WHO threshold was reached by 2061. Other scenarios modeled future changes in HPV DNA-based screening rates with either 50% or 90% vaccination coverage. The 75% HPV DNA-based screening with 90% vaccination coverage scenario reached the WHO threshold by 2047 and the eradication threshold before the end of the century (2096).ConclusionIf public health interventions are implemented to accelerate HPV vaccination coverage and HPV DNA-based screening adherence within the next five years, Greece can reach the WHO’s cervical cancer elimination threshold by 2047 and eradicate cervical cancer before the end of the century.